2015
DOI: 10.5194/angeo-33-1011-2015
|View full text |Cite
|
Sign up to set email alerts
|

Profile of a low-Mach-number shock in two-fluid plasma theory

Abstract: Abstract. Magnetic profiles of low-Mach-number collisionless shocks in space plasmas are studied within the two-fluid plasma theory. Particular attention is given to the upstream magnetic oscillations generated at the ramp. By including weak resistive dissipation in the equations of motion for electrons and protons, the dependence of the upstream wave train features on the ratio of the dispersion length to the dissipative length is established quantitatively. The dependence of the oscillation amplitude and spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…More importantly, we demonstrate that the ramp and precursors display a quasi-perpendicular geometry. This finding is in line with theoretical predictions (Gedalin 1998;Gedalin et al 2015), which suggest that a quasi-parallel shock becomes oblique, even quasi-perpendicular, due to the increase in transversal magnetic field amplitude in the ramp-overshoot region. However, prior to our study, observational support for this was limited (Balikhin et al 2023).…”
Section: Structure Of the Quasi-parallel Shock Transitionsupporting
confidence: 92%
“…More importantly, we demonstrate that the ramp and precursors display a quasi-perpendicular geometry. This finding is in line with theoretical predictions (Gedalin 1998;Gedalin et al 2015), which suggest that a quasi-parallel shock becomes oblique, even quasi-perpendicular, due to the increase in transversal magnetic field amplitude in the ramp-overshoot region. However, prior to our study, observational support for this was limited (Balikhin et al 2023).…”
Section: Structure Of the Quasi-parallel Shock Transitionsupporting
confidence: 92%
“…Low Mach number shocks in the heliosphere are also usually approximately planar and stationary. Based on these conditions and following Gedalin et al (2015), two-fluid plasma theory should be an appropriate analytical approach to study the shock front structure. Within this approach, we consider a one-dimensional stationary plasma where all variables depend only on the coordinate x along the shock normal.…”
Section: The Upstream Magnetic Field From the Two-fluid Plasma Modelmentioning
confidence: 99%
“…Yet, upstream of the ramp the two-fluid approach is still a good approximation. It was shown that even if restricting for the upstream region only, stationary solutions with decaying oscillations exist only if dissipation is invoked (Gedalin, Kushinsky & Balikhin 2015 b ). This brings us to the conclusion that even low-Mach shocks may be intrinsically non-stationary and generate upstream propagating whistler wave trains.…”
Section: Introductionmentioning
confidence: 99%